Efforts to increase students' involvement in the english learning in class 1 SMU N 2 Yogyakarta In The Academic year of 2003/2004 / Shanti Apriliayani - SHANTI APRILIYANI; GUNAWAN (State University of Yogyakarta, 2004)
x, 141 lembar ; 29,5 cm